Translanguaging Joyce: monolingual disruptions and translingual enrichment in Ulysses. Issue 2 (1st February 2022) - Miller, E. Paige
ABSTRACT: James Joyce's Ulysses draws attention to spaces of language contact in which the boundaries between languages are fluid and contingent. While multilingualism has long been a subject of fruitful research in Joyce studies, much of this scholarship continues to rely on notions of discrete, named languages that uphold a monolingual paradigm. By bringing together theories of the 'postmonolingual condition' (Yildiz) and linguistics scholarship on translingualism (Canagarajah) and translanguaging (García and Wei), I contextualise two related but separate terms – multilingualism and translingualism – and their assumptions regarding language use within literary studies and Joyce studies. Whereas a multilingual methodology preserves the assumption of languages as discrete entities, a translingual approach asserts that individuals are constantly moving among or between languages. Thus, when Joyce's characters slip across a perceived linguistic border – an act that I interpret as a form of literary translanguaging – the integrated use of multiple linguistic resources combine to enrich rather than disrupt their idiolect. By reframing language production as fluid and dynamic while also drawing attention to the sociopolitical realities of the 'postmonolingual paradigm', I argue that a translingual approach to Ulysses at its centenary captures the rich performances of speaker identity through and across multiple languages, modes, and senses.